THE MAKE A MATCH MODEL AT THE COGNITIVE LEVEL OF ANALYZING (C4): HOW DOES IT CONTRIBUTE TO LEARNING OUTCOMES? - Andelina Damayanti; Syaiful Anwar; M. Indra Saputra; Baharudin Baharudin (Reflektika, 2025)
Ideally, Islamic Religious Education (IRE) should develop students’ analytical thinking skills at the C4 cognitive level. However, the learning process at SMA Negeri 1 Abung Semuli is still dominated by monotonous lecturing, resulting in low student engagement, difficulty in analyzing religious concepts, and an inability to relate the material to real-life contexts. This situation leads to low learning outcomes, particularly on tasks that require analytical skills. Based on these issues, this study aims to examine the effectiveness of the Make-a-Match type of Cooperative Learning in improving PAI learning outcomes, specifically in the C4 cognitive domain. The study employed a quantitative approach with involving two Grade X classes: an experimental class that received the Make-a-Match treatment and a control class that was taught using conventional methods. The learning outcome test instrument consisted of 15 questions that were validated and tested for reliability, and subsequently used in both pre-tests and post-tests. Data were analyzed using normality and homogeneity tests, Mann–Whitney, and independent t-tests according to the data distribution characteristics. The results indicated a significant difference between the experimental and control classes. The Mann–Whitney test yielded a significance value of 0.012, while the independent t-test yielded 0.013 (< 0.05), indicating that the Make-a-Match model has a positive effect on improving students’ learning outcomes. The card-matching activities encouraged students to analyze, compare concepts, and identify material relationships more critically, thereby enhancing C4-level abilities. In conclusion, the Make-a-Match type of Cooperative Learning is effective in improving PAI learning outcomes, particularly students’ analytical skills. This model is recommended as an innovative and interactive instructional strategy to enhance the quality of PAI learning in senior high schools